UNNES Green Transportation as a Continuous Effort in Building a Conservation University - Fathur Rokhman; Hendi Pratama; Amin Retnoningsih (Universitas Diponegoro, 2021)
Universitas Negeri Semarang (UNNES) declared itself as a conservation university with 3 main pillars, namely: (1) values and character, (2) arts and culture, and (3) natural resources and physical environment. UNNES believes the environmental crisis cannot be overcome only through practical and technical actions but it also attempts to change the way humans view and behave towards the environment. One indicator of natural resources pillars and the environment is green transportation. To implement green transportation, UNNES develops an internal transportation system to guide the use of vehicles, roads and parking areas on the campus. The use of regulated vehicles included motorized and non-motorized vehicles. The target of implementing a green transportation system was to reduce emissions in the campus environment to a minimum level. Motorized vehicles must obey the directional traffic signs applied in the campus environment and be only allowed to park in designated parking areas. Sufficient space for bicycle traffic, environmentally-friendly vehicles, and pedestrians on the sideways were preferred. Motor vehicle noise levels must not exceed 55 dB. Special vehicle traffic, among others, such as garbage transporters, watering plants, fire engines, and special-licensed vehicles were regulated under applicable regulations. Inspection tasks were carried out by security vehicles that can go through all roads in the campus environment in the direction of the designated lane, except in unlikely emergencies. Environmentally-friendly vehicles in the form of electric and non-fossil cars operated on Monday-Friday from 6:00 to 18:00 and were free. Markings with different colors, and bicycle lanes were used to differentiate between motorized vehicles. Campus parking points consisted of a central parking point and several auxiliary parking units. The central parking in the Multi-purpose Building was used for motorized vehicles or bicycles and was guarded 24 hours. Meanwhile, the auxiliary parking units were located in each work unit area which also had a security system. People with disabilities were facilitated through special signposts.